The Effectiveness of Concept Mapping–Based Shorof Instruction in an Islamic Boarding School Context - Siti Mahmudah S.; Suliman H. Suliman El Warfali; Zeid B. Smeer (Nurul Jadid University, 2025)
The instruction of Sharaf in many Islamic boarding schools remains dominated by teacher-centered and memorization-based methods, resulting in low student engagement and limited conceptual mastery. This study aims to examine the effectiveness of the concept mapping method in improving students’ learning outcomes and motivation in shorof instruction. Employing a mixed-methods approach with an embedded quasi-experimental design, the research was conducted at the Islamic Boarding School , involving 24 third-semester students divided into experimental and control groups. Data were collected through observations, interviews, pretests, posttests, questionnaires, and documentation. The findings reveal a significant improvement in the experimental class, with the average score increasing from 63.42 to 90.50, compared to the control class (71.67 to 80.67). Statistical analysis confirmed effectiveness (sig. = 0.014 < 0.05), supported by a high student satisfaction rate (90.3%). This study contributes empirical evidence on the application of concept mapping in shorof learning and recommends its integration into pesantren-based Arabic instruction to enhance conceptual understanding and learner engagement.